Pengembangan Sistem Informasi Berbasis Enterprise Resource Planning (ERP) dalam Integrasi Data Perusahaan - Rizky Maulana Firdaus; Ahmad Amrullah; Husnul Mukarromin; Alfan Maulidi; Bagus Putra Ramadhani; Yeni Tri Nur Rahmawati (Jurnal Manajemen dan Ilmu Administrasi, 2026)
Data silos or information barriers between departments are often the main obstacle to rapid and accurate decision-making in the digital era. This research aims to design and analyze the development of an Enterprise Resource Planning (ERP)-based Information System in integrating corporate operational data. Utilizing a descriptive qualitative approach and literature review, this study explores the stages of ERP implementation, ranging from planning to post-implementation evaluation. The results indicate that ERP integration successfully eliminates data redundancy, enhances real-time information transparency, and accelerates internal bureaucratic efficiency by 35%. However, the primary challenge lies in human resource resistance to the new system changes. It is concluded that the success of ERP relies not only on technological readiness but also on effective change management and strong leadership commitment.